2017
DOI: 10.1038/s41598-017-08231-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neuronal pathfinding and construction of artificial neuronal networks on 3D-arranged porous fibrillar scaffolds with controlled geometry

Abstract: Herein, we investigated the neurite pathfinding on electrospun microfibers with various fiber densities, diameters, and microbead islands, and demonstrated the development of 3D connected artificial neuronal network within a nanofiber-microbead-based porous scaffold. The primary culture of rat hippocampal embryonic neurons was deposited on geometry-controlled polystyrene (PS) fiber scaffolds while growth cone morphology, neurite outgrowth patterns, and focal adhesion protein expression were cautiously examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In 2017, Kim et al investigated a different technique, termed electrospinning, in order to develop a 3-D connected artificial neuronal network within a nanofiber-microbead-based porous scaffold. This inspiring scaffold allowed substantial neurite outgrowth in a vertical direction [ 121 ].…”
Section: Geometriesmentioning
confidence: 99%
“…In 2017, Kim et al investigated a different technique, termed electrospinning, in order to develop a 3-D connected artificial neuronal network within a nanofiber-microbead-based porous scaffold. This inspiring scaffold allowed substantial neurite outgrowth in a vertical direction [ 121 ].…”
Section: Geometriesmentioning
confidence: 99%
“…Live‐cell imaging has also been used to demonstrate that cytosolic calcium signatures change dynamically in mesenchymal stem cells undergoing osteoblastic differentiation (Franz, Karagaraj, & Sun, 2014). More recently, Han, Wu, Xia, Wagner, and Xu (2016) and D. Kim, Kim, Lee, and Yoon (2017), in independent studies, used confocal imaging to evaluate intracellular calcium responses in cells cultured on electrospun matrices. However, both studies evaluated calcium dynamics over short periods and neither study performed volumetric imaging of calcium spiking.…”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning can be employed to create porous three-dimensional structures to which cells can adhere, proliferate, grow, and differentiate in order to repair and replace damaged tissue [109][110][111]. Kim et al [7] demonstrated that the morphological factors of electrospun fibers have a significant effect on the growth mode of neuronal cells by showing that neurites grow along the direction of the fibers, subsequently decreasing the linearity of the neurites when fiber density increases. Wang et al [12] fabricated three-dimensional polymer scaffolds with mechanical properties similar to tendons with controllable anisotropic microstructures, which could be used to deliver drugs or for tissue regeneration.…”
Section: Recent Biological and Medical Engineering Applicationsmentioning
confidence: 99%
“…Materials made from electrospinning technology (EST) have been created for use in a variety of applications in several fields due to their small diameter, large specific surface, and high porosity [1][2][3][4][5]. For instance, nanofibers created from electrospinning technology can be used for biological engineering, pollution treatment, and as sustainable energy materials [6][7][8][9][10][11][12][13]. Electrospinning technology refers to a method in which a polymer solution or a melt is spray-stretched and then volatilized or melt-cured in order to create an ultrafine fiber using a high-voltage electrostatic force.…”
Section: Introductionmentioning
confidence: 99%